The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0145397
|View full text |Cite
|
Sign up to set email alerts
|

Differential Toll-Like Receptor-Signalling of Burkholderia pseudomallei Lipopolysaccharide in Murine and Human Models

Abstract: The Gram-negative bacterium Burkholderia pseudomallei causes melioidosis and is a CDC category B bioterrorism agent. Toll-like receptor (TLR)-2 impairs host defense during pulmonary B.pseudomallei infection while TLR4 only has limited impact. We investigated the role of TLRs in B.pseudomallei-lipopolysaccharide (LPS) induced inflammation. Purified B.pseudomallei-LPS activated only TLR2-transfected-HEK-cells during short stimulation but both HEK-TLR2 and HEK-TLR4-cells after 24 h. In human blood, an additive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…We agree with the finding of others that the O-antigens of B. multivorans contribute to TLR4/MD2-mediated signaling and consequently lead to production of high concentrations of inflammatory cytokines (44). Furthermore, the unique acyl 2-hydroxytetradecanoic acid in lipid A from B. pseudomallei LPS or the Ara4N substitution in the core sugars of B. cenocepacia LPS decrease the degree to which the CD14-TLR4-MD2 interaction is achieved (4,20,45). When we compared the genome-related strains, we found that exposure to B.…”
Section: Discussionsupporting
confidence: 92%
“…We agree with the finding of others that the O-antigens of B. multivorans contribute to TLR4/MD2-mediated signaling and consequently lead to production of high concentrations of inflammatory cytokines (44). Furthermore, the unique acyl 2-hydroxytetradecanoic acid in lipid A from B. pseudomallei LPS or the Ara4N substitution in the core sugars of B. cenocepacia LPS decrease the degree to which the CD14-TLR4-MD2 interaction is achieved (4,20,45). When we compared the genome-related strains, we found that exposure to B.…”
Section: Discussionsupporting
confidence: 92%
“…The deacylation of Y. pestis and F. tularensis lipid A at human body temperature exemplifies a pathoadaptive capacity. Tetra-acylated lipid A is frequently observed in lipid A isolated from B. mallei , B. pseudomallei , and B. thailandensis ( 30 , 42 , 43 ) alongside penta-acylated lipid A, so it is likely that a pagL homologue exists in B. pseudomallei to enzymatically modify the parental penta-acylated lipid A ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The structure was reproduced from Kawasaki et al ( 40 ) and Gibbons et al ( 52 ). (B) Current B. pseudomallei lipid A structure from the literature, with assumed PagL and LpxO modifications ( 30 , 33 , 43 , 51 ). Carbon lengths of acyl chains are indicated below each chain.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that TLR’s play a significant role in host susceptibility to melioidosis [13, 1618]. A broader study to determine TLR receptor expression and signaling pathways could provide insights for understanding disease susceptibility and progression following B .…”
Section: Introductionmentioning
confidence: 99%